Sistem Informasi Keanggotaan Aslab Studi Kasus GI-BEI Polinema PSDKU Di Kota Kediri Berbasis Web - Satrio Sarwo Utomo (Politeknik Negeri Malang, 2022)
Aslab GI-BEI is a laboratory assistant under the authority of the accounting study program at the PSDKU POLINEMA campus in Kediri City. GI BEI PSDKU Polinema In the City of Kediri currently does not have an information system to manage membership data in an integrated manner, the management of activity data still uses manual methods, such as archiving in the notebooks of each member of the organization, so that the data collection of registrants and members is not integrated with each other . Membership data that are not integrated with each other will cause a lack of efficiency in managing membership data. So it is necessary to design and build a Web-Based Aslab Membership Information System GI-BEI Polinema Psdku Case Study in Kediri City. The main purpose of developing this membership management information system is to make membership data management more efficient. This membership management information system is built in the Laravel framework based on the PHP programming language and uses the MySQL database. This membership management information system has 2 users, the chairman of the GI-BEI, and the GI-BEI supervisor. Application features consisting of membership management, registrant management, membership detail management, member structure management, and registrant status validation have been tested and succeeded as expected.